Deformation and cyclic behavior of partially-restrained energy dissipaters with yielding end connections. (July 2022) - Shi, Hai-Rong; Yuan, Yue; Qing, Yuan; Wang, Chun-Lin; Liu, Ye
Abstract: Partially-restrained Energy Dissipater (PED) is a metal hysteresis dissipative device and exhibits an excellent low-cycle fatigue performance. Each PED typically consists of an inner core and an outer restraining member. The inner core is manufactured from a steel rod, forming a milled portion (the fuse) to dissipate energy and two intact external portions (external bars) to connect with structural members. External bars were expected to remain elastic in prior studies and the cyclic responses of PEDs with yielding external bars were hardly discussed. In this paper, a total of eight PEDs were designed and tested to comprehensively investigate the hysteresis responses of PEDs with yielding external bars. The three variable parameters of the test were loading patterns, the unrestrained length of the external bar l ur and the cross-sectional area ratio ρ of the fuse to the external bar. The test results illustrated that most of PEDs exhibited stable cyclic performances after external bars yielding and two failure modes were observed, including fuse fracture and end bending. Besides, a larger area ratio ρ significantly improved the low-cycle fatigue life and energy dissipation capacity of PEDs, meanwhile it increased the demand on the flexural stiffness of the external bar to avoid end bending. Finally, an analytical model was established for the deformation of the external bar and a design criteria was presented to avoid the end bending failure of PEDs with yielding end connections Highlights: PEDs exhibited stable hysteresis behaviors after end connections yielding. A larger area ratio of the yielding portion to external bars can be adopted. Low-cycle fatigue life of PEDs is improved by increasing the area ratio. A design criteria is proposed to avoid the excessive bending of inelastic external bars.